Foxes and Hen Houses?: Personal Trading by Mutual Fund Managers - Edward B. Rock (Washington University Law Quarterly, 1995)
In this Article, I examine the regulation of personal trading by money managers as a vehicle for better understanding the bases and strategies for regulating money managers in general.
Keywords: Mutual funds